Integrated Transcriptomic and Translatomic Inquiry of the Role of Betaine on Lipid Metabolic Dysregulation Induced by a High-Fat Diet - Huang, Tengda; Yu, Lin; Pan, Hongyuan; Ma, Zeqiang; Wu, Tian; Zhang, Lifang; Liu, Kang; Qi, Qi; Miao, Weiwei; Song, Ziyi; Zhang, Haojie; Zhou, Lei; et al. (Frontiers in Nutrition, 2021)
An excessive high-fat/energy diet is a major cause of obesity and linked complications, such as non-alcoholic fatty liver disease (NAFLD). Betaine has been shown to effectively improve hepatic lipid metabolism. However, the mechanistic basis for this improvement is largely unknown. Herein, integration of mRNA sequencing and ribosome footprints profiling (Ribo-seq) was used to investigate the means by which betaine alleviates liver lipid metabolic disorders induced by a high-fat diet. For the transcriptome, gene set enrichment analysis demonstrated betaine to reduce liver steatosis by up-regulation of fatty acid beta oxidation, lipid oxidation and fatty acid catabolic processes. For the translatome, 574 differentially expressed genes were identified, 17 of which were associated with the NAFLD pathway. By combined analysis of transcriptome and translatome, we found that betaine had the greater effect on NAFLD at the translational level. Further, betaine decreased translational efficiency (TE) for IDI1, CYP51A1, TM7SF2, and APOA4, which are related to lipid biosynthesis. In summary, this study demonstrated betaine alleviating lipid metabolic dysfunction at the translational level. The transcriptome and translatome data integration approach used herein provides for a new understanding of the means by which to treat NAFLD.